Assessing water surface temperature from Landsat imagery and its relationship with a nuclear power plant. Issue 1 (2nd January 2021) - Bonansea, Matias; Ferrero, Susana; Ferral, Anabella; Ledesma, Micaela; German, Alba; Carreño, Joel; Rodriguez, Claudia; Pinotti, Lucio
ABSTRACT: Water temperature is fundamental to understand the functioning of aquatic systems. The objective of this study was to assess the effect of warm water discharge from a nuclear power plant on the water surface temperature (WST) of a reservoir. Using a 6-year Landsat-derived WST dataset, which includes 3 years of the power plant being in operation (2013–2015) and 3 years in which the power plant was not functioning (2016–2018), the effect of the thermal pollution was assessed. The results show that, although the warm water discharge did not reveal a statistically significant increase on the mean WST of the reservoir ( p > 0.05), multi-temporal Landsat imagery revealed that the power plant generated a local thermal impact. This was the principal heat flux following a dissipation line that was wide near the cooling channel and expanding towards the rest of the reservoir.